Pulmonary Hypertension In Indonesia: Where and How is the Data? What is the Gaps? - Bambang Budi Siswanto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Pulmonary Hypertension In Indonesia: Where and How is the Data? What is the Gaps?